On the Creation Theory and the Issue of Nihilism in Arabic-Islamic Philosophy - Kasumović, Ismet (Prilozi za orijentalnu filologiju, 2017)
In the broad scope of issues considered in Arabic-Islamic philosophy of ta- şawwuf, issues thought to be signifıcant for the establishment of “Isiamic ontological realism”, the creation theory occupies an important place. Occu- pyiııg the middle ground between Arabic-Islamic philosophy on the one hand, and the members of Kalâm school on the other, the issue of the creation was in this environment subject of polemic and differentiatioıı amongst the philosophers (the works of Al-Ghazali, for instance) usuaily resulting in radical approaches to the Book’s appreciative understanding which came as a necessity in certaiıı social and historical circumstances and practice. The way in which this issue developed and was articulated in Arabic- Islamic philosophy was, however, highly distinctive and varied from thinker to thinker although for the point of departure most of them used the same monotheistic principle of at-tawhîd \vhich was of the basic principies of their scholastic and philosophical efforts. The reason for this can usuaily be found in the opposing influences worked upon them by the ancient Greek and Indo-Iranian philosophy as well. Because the creation theory in İslam is based on the well-known view- point of creation ex nihilo (al-halq mina l~'adam), as opposed to the meta- physical viewpoint of ex nihilo nihili fit, these thinker attempted to solve that logical dilemma in a painless way by bridging the gap between religion and philosophy, as well as by providing a logical justification to religious atti- tudes. These attempts are, in fact, the subject of investigation of this essay whose purpose is to examine the emergence of the creation theory from the earliest endeavors as to interpretation of the Qur’an on the pert of the pio- neers of the hermeneutic approach to Qur’an. In the fuıther analysis, our purpose was to shad the light on the mu‘tazilits, the issue of rationality of being and the teachings on being and nonbeing which was, amongst other things, the rational for their disquaIifıcation and the fractions within the school of Kalâm. This is followed by the Al-Guwayni and Al-Baqilâni’s elaboration of their teachings as to the modus as the middle between being and nonbeing, or the state of emergence and linguistic analysis of the notion of the creation. In the school of Falâsifa, however, this issue was articulated through the avoidance of objectifıcation according to Piotinus’ theory of emanation which was, in somewhat modified form though, supported by Al-Kindi, Al-Farabi, Ibn Sina and other philosophers who established a middle-ground theory corre- sponding to the Qur’anic notion of ‘âlamu l-malaküt as opposed to Al-Ghazali who represented the viewpoint of creatio ex nihilo in accordance with the eternal will in which the area of nonbeing appears as transtemporal unlike the world of being which is temporal. Ibn Rushd’s attempts are, hovvever, based on the same attitude although with him this problem was founded on the Aristotelian teachings on potentiality and actuality so nonbeing was un- derstood as a possibility eternally inherent to the primordial matter (hayülâ), or the Aristotelianprivatio. Unlike Ibn Rushd, the members of tasawwuf solved this problem by means of the emanation and demonstration theories in which the creation was re- garded as a continuous process and flow in the hierarchical scale of beings from the One towards the world which is the only reality in appearance (al-haqq fi z-zuhür). As the majority of above-mentioned attempts were based on the primary principle of at-tawhid scale and also regarded as a problem as to the seeking the rational justification of the above principle, we can say that fundamenta! for ali of these attempts is the effort resulted in inauguration of Essential Existence, which is eternal, as opposed to the Potential Existence which be- longs to the world of transience {hawadit) created from the Nothing and it only represent a reflection of the divine existence. This poses a question of rationality of existence and the creation theory serves as to the understanding of the above-mentioned principle.